On Extended b-Rectangular and Controlled Rectangular Fuzzy Metric-Like Spaces with Application. (18th July 2022) - Saleem, Naeem; Furqan, Salman; Jarad, Fahd
Abstract : In this article, we introduce the notions of extended b -rectangular and controlled rectangular fuzzy metric-like spaces that generalize many fuzzy metric spaces in the literature. We give examples to justify our newly defined fuzzy metric-like spaces and prove that these spaces are not Hausdorff. We use fuzzy contraction and prove Banach fixed point theorems in these spaces. As an application, we utilize our main results to solve the uniqueness of the solution of a differential equation occurring in the dynamic market equilibrium.